Development of blast resistant somaclones of the upland rice cultivar Araguaia - Araújo, Leila Garcês de; Prabhu, Anne Sitarama; Freire, Adelson de Barros (Pesquisa Agropecuaria Brasileira, 2000)
The degree of blast resistance of upland rice (Oryza sativa L.) cultivar Araguaia has decreased over time causing significant yield losses. The major objective of this study was to obtain blast (Pyricularia grisea) resistant somaclones, adapting greenhouse and field selection procedures. Rice blast resistance and agronomic traits were assessed in R2 to R6 generations derived from regenerant plants (R1) from immature panicles of Araguaia. The evaluation and selection procedures include testing of early segregating populations and fixed lines in the advanced generations, under natural field conditions, and artificial inoculations in the greenhouse, with prevalent races IB-1 and IB-9 of P. grisea. Somaclones with both vertical resistance and slow blasting resistance were obtained. Twenty of 31 somaclones developed with a high degree of vertical resistance and fan shaped plant type maintained resistance in field and blast nursery tests in the R6 generation. Greenhouse selection with two specific physiologic races yielded 44 somaclones with slow blasting resistance, similar plant type and yield potential as that of Araguaia.